An integrated software quality model in a fuzzy analytical hierarchy process-based evaluation framework for e-learning software / Ahmad Fadli Saad - Ahmad Fadli , Saad (2017)
The demand in implementing e-Learning in organisations has triggered the emergence of numerous e-Learning software (e-LS). Thus, it is necessary for organisations to select the correct e-LS for use within their organisations. The evaluation and selection of the e-LS can be complex and difficult because it involves many processes which are related to the evaluation criteria and the evaluation technique. For this purpose, the Software Quality Model (SQM) such as the ISO/IEC 9126-1 Quality Model can be used as a reference as it offers a list of criteria which encompass Functionality, Usability, Maintainability, Efficiency, Portability and Reliability. These are commonly used as criteria for evaluating the e-Learning software. In addition to this, the Commercial-Off-The Shelf (COTS) framework is also useful although it provides a different set of criteria such as Cost, Vendor, Product Benefits, Risk and Uncertainty and Organizational. It commonly uses the Multi Criteria Decision Making (MCDM) technique which includes the Analytical Hierarchy Process (AHP) for any software evaluation. The limitation of the AHP is its inability to handle any uncertain criteria in the evaluation process implying that there is no adequate evaluation framework that can currently be applied to evaluate the e-LS more appropriately. This is because the important criteria and sub-criteria that can be used to evaluate the e-LS have not been adequately identified. This study attempts to formulate an evaluation framework that can be adequately used for the e-LS evaluation. The framework incorporates the e-LS quality model which comprises the important criteria for evaluating the e-LS. The framework developed in this study is supported by a tool that is based on the Fuzzy AHP technique which addresses the limitation of the AHP. More than 250 related articles and references were reviewed for the purpose of identifying the key criteria for the e-LS evaluation. The Delphi survey was conducted to obtain a list of additional criteria based on the consensus of 31 local e-Learning experts. A total of 11 criteria and 66 sub-criteria were extracted from literature review while 16 additional sub-criteria were provided by the experts. In total, 11 criteria and 81 sub-criteria were validated by the experts‘ consensus. Based on this, an Integrated Software Quality Model (ISQM) was then constructed. An e-LS evaluation framework consolidating the ISQM with the Fuzzy AHP technique, namely the ISQM-Fuzzy AHP, was then formulated. The tool, called the e-LSO, was then developed to assist in the e-LS evaluation. A usability evaluation of the e-LSO was tested via the Post-Study System Usability Questionnaire (PSSUQ) involving five e-LS experts. The results revealed that the experts were satisfied with the e-LSO and they also approved of it as a useful tool for the e-LS evaluation. Overall, it can be said that the ISQM-Fuzzy AHP can serve as a guideline and support for organisations in their e-LS evaluation processes. The e-LSO can also assist organisations to create their own decision models for the e-LS evaluation easily.